Two new chemical constituents from the stem bark of Garcinia mangostana - See, Irene; Ee, Gwendoline Cheng Lian; Teh, Soek Sin; Abdul Kadir, Arifah; Daud, Shaari (MDPI, 2014)
A detailed chemical study on the ethyl acetate and methanol extracts of the stem bark of Garcinia mangostana resulted in the successful isolation of one new prenylated xanthone, mangaxanthone B (1), one new benzophenone, mangaphenone (2), and two known xanthones, mangostanin (3) and mangostenol (4). The structures of these compounds were elucidated through analysis of their spectroscopic data obtained using 1D and 2D NMR and MS techniques.